2015
DOI: 10.1111/acel.12379
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antidepressants extend lifespan of Caenorhabditis elegans by activation of a non‐cell‐autonomous stress response

Abstract: SummaryOxidative stress has long been associated with aging and has recently been linked to psychiatric disorders, including psychosis and depression. We identified multiple antipsychotics and antidepressants that extend Caenorhabditis elegans lifespan and protect the animal from oxidative stress. Here, we report that atypical antidepressants activate a neuronal mechanism that regulates the response to oxidative stress throughout the animal. While the activation of the oxidative stress response by atypical ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 45 publications
(60 reference statements)
2
28
0
Order By: Relevance
“…Our results indicate that both the deficiency of 5-HT, as well as its excess cause global changes in the transcriptome predicted to affect numerous tissue-types. While the RNA-seq datasets presented here show good agreement with published transcriptomes from animals treated with a 5-HT antagonist, mianserin (Rangaraju et al 2015a;Rangaraju et al 2015b), Gene Ontology analysis and comparison with the various published transcriptomes showed that gene expression changes in animals with excess 5-HT correlates best with gene expression changes from animals that have activated defense responses, and RNA-seq data from tph-1 (mg280) II animals was enriched for genes related to development and chromatin function. In addition, comparisons of the transcriptomes of animals with excess 5-HT or 5-HT deficiency (tph-1 (mg280) II) and published transcriptional profiles of C. elegans mutants which they phenotypically resemble, showed no significant overlap, suggesting that the similarity in the phenotypes of these animals may stem from commonalities other than gene expression changes.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Our results indicate that both the deficiency of 5-HT, as well as its excess cause global changes in the transcriptome predicted to affect numerous tissue-types. While the RNA-seq datasets presented here show good agreement with published transcriptomes from animals treated with a 5-HT antagonist, mianserin (Rangaraju et al 2015a;Rangaraju et al 2015b), Gene Ontology analysis and comparison with the various published transcriptomes showed that gene expression changes in animals with excess 5-HT correlates best with gene expression changes from animals that have activated defense responses, and RNA-seq data from tph-1 (mg280) II animals was enriched for genes related to development and chromatin function. In addition, comparisons of the transcriptomes of animals with excess 5-HT or 5-HT deficiency (tph-1 (mg280) II) and published transcriptional profiles of C. elegans mutants which they phenotypically resemble, showed no significant overlap, suggesting that the similarity in the phenotypes of these animals may stem from commonalities other than gene expression changes.…”
supporting
confidence: 71%
“…The transcriptomes of both tph-1 animals and animals with excess 5-HT overlap significantly with animals treated With the atypical antidepressant, mianserin To authenticate our RNA-seq analysis we compared our RNA-seq data with the transcriptomes of animals where 5-HT levels were modulated through alternative means, namely by treatment with the 5-HT receptor antagonist, mianserin (Rangaraju et al 2015a;Rangaraju et al 2015b). Mianserin is used as an atypical antidepressant in humans, and increases lifespan and modulates transcriptional drift in C. elegans by acting through 5-HT pathways (Rangaraju et al 2015a;Rangaraju et al 2015b). In accordance with the role of mianserin as a 5-HT antagonist, the transcriptional changes in tph-1 animals significantly overlapped those animals treated with mianserin for 5 and 10 days as adults (P = 6.95 e-5, P = 1.36 e-11) ( Figure 10A,B).…”
Section: The Chronic Lack Of Serotonin Causes a Net Increase In Gene mentioning
confidence: 99%
“…Because the expression patterns observed in many GOs were difficult to interpret in terms of functional change, we turned to investigate expression changes in the superoxide detoxification pathway, a well-defined cellular function that declines with age (Ashburner et al, 2000;Mi et al, 2005;Kumsta et al, 2011;Bansal et al, 2015;Rangaraju et al, 2015a). As expected from our previous studies (Rangaraju et al, 2015a), the expression levels of some superoxide detoxification genes were higher in mianserin-treated animals compared to age-matched controls ( Figure 1d). Exceptions were the expression levels of sod-4 and sod-5, which were lowered upon mianserin treatment ( Figure 1d).…”
Section: Aging Causes a Loss Of Co-expression Patterns Observed In Yomentioning
confidence: 68%
“…When we excluded all genes that changed due to age and were attenuated by mianserin, we obtained a much smaller gene-set consisting of mianserin-induced changes that was enriched for GOs related to stress, xenobiotic and immune-responses, as well as genes associated with aging and the determination of lifespan (Table 1, Figure 1-source data 5). These GOs have been previously shown to be regulated by serotonin in C. elegans with the exception of the xenobiotic response (Zhang et al, 2005;Petrascheck et al, 2007;Rangaraju et al, 2015a). Thus, accounting for age-associated transcriptional changes dramatically simplified a seemingly very complex geneexpression pattern (Figure 1b,c).…”
Section: Aging Causes a Loss Of Co-expression Patterns Observed In Yomentioning
confidence: 83%
See 1 more Smart Citation